Pengaruh Pola Asuh Orangtua terhadap Perkembangan Psikososial Anak Menurut Kepribadian Erik H. Erikson - Fadilah, Risydah; Putri, Junita Hanum Eka; Nurfaridah, Kharisma; Marselina, Lisna (YASIN, 2023)
The development of a child can never be separated from the social environment. The child's social environment in question is the family and social group. Many cases of concern are related to family conditions or social group conditions that cause an identity crisis (identity crisis) in children. For example, the case of a child who is neglectful, unenthusiastic and doesn't even respect other people in the environment around him because of the influence of gadgets and negligent parenting. This research will focus on discussing the Analysis of the Effect of Parenting on Children's Psychosocial Development (Case Study on Students (15 years) at SMP 02 Batang Kuis Satu Atap, Kapubaten Deli Serdang). apply proper parenting and be able to understand their children according to their development and parents can apply parenting styles that are appropriate to the stages of child development. Based on the results of the study, it was concluded that children who are raised with neglectful parenting tend to have difficulty self-regulating in socializing. This is as a result of parenting patterns that do not support children to have independence. Based on these factors, we can see that Psychosocial Personality in Children is the result of a lifelong learning process obtained from the family and environment which is interpreted differently in individuals. During the process of development, individuals learn from the family environment from birth. In this case, parents have a great influence to create an environment for children, both in personal care and with the help of others.